Adenocarcinoma of humerus shaft treated with en bloc excision and long locking compression plate with fibular strut and iliac bone grafting: a case report - Bhuti, Gangadhar; Chowkimath, Shivaprasad; Pratap, Aditya; Samanta, Tathagata; Paled, Kirankumar (International Journal of Research in Orthopaedics, 2025)
Adenocarcinoma of the humerus shaft is a rare malignant tumor, often secondary to metastasis from a primary site such as the lung, breast, or gastrointestinal tract. Management of these cases is challenging due to the complex anatomy, the need to preserve limb function, and the high risk of recurrence. This case report highlights a unique approach involving en bloc excision, long locking compression plate (LCP) fixation, fibular strut grafting, and iliac bone grafting. A 55-year-old female presented with persistent pain and swelling in the midshaft of right humerus, accompanied by reduced range of motion. Imaging revealed a lytic lesion, and biopsy confirmed metastatic adenocarcinoma. After a multidisciplinary evaluation, an en bloc excision of the tumor was performed. Reconstruction involved internal fixation with a long LCP, augmented by a vascularized fibular strut graft and autologous iliac bone grafting. Postoperative care included adjuvant chemotherapy and physiotherapy. Postoperative outcomes were favorable, with evidence of graft integration and functional recovery at six months, alongside significant pain reduction and absence of local recurrence at one-year follow-up. The combination of biological and mechanical reconstruction techniques provided durable outcomes and restored limb function. This report underscores the importance of a multidisciplinary approach and highlights the efficacy of autograft-based biological reconstruction in managing extensive diaphyseal defects. The chosen method demonstrates a viable alternative to endoprosthetic reconstruction, particularly in patients with long-term survival potential.